Biological activity of heterologous murine interleukin-10 and preliminary studies on the use of a dextrin nanogel as a delivery system - Carvalho, Vera (2010)
Interleukin-10 (IL-10) is an anti-inflammatory cytokine, which active form is a non-covalent homodimer with two intramolecular disulphide bonds essential for its biological activity. A mutated form of murine IL-10 was successfully expressed in E. coli, recovered and purified from inclusion bodies. Its ability to reduce tumor necrosis factor synthesis and down-regulate class II major histocompatibility complex molecules expression on endotoxin-stimulated bone marrow-derived macrophages was confirmed, and shown to be similar to that of a commercially available IL-10. Given the potential of IL-10 for application in various medical conditions, it is essential to develop systems that can effectively deliver the protein. In this work it is shown that a dextrin nanogel effectively incorporate IL-10, stabilize, and enable the slow release of biologically active IL-10 over time. Altogether, these results demonstrate the suitability of dextrin nanogel to be used as a system for the controlled release of IL-10.